Correlation and mechanism between cardiac magnetic resonance imaging and oral streptococcus count in patients with primary microvascular angina pectoris. Issue 12 (25th March 2022) - Huang, Qi; Wang, Shi Sheng; Luo, Rong Hua
Abstract: Background: Although primary microvascular angina (PMVA) can be diagnosed clinically, the etiology and pathophysiology of PMVA remain unclear. The effects of conventional clinical medications (aspirin, statins, and nitrates) are unsatisfactory, and PMVA can lead to serious cardiovascular events. The present study was designed to analyze the correlation between the load perfusion cardiovascular magnetic resonance imaging (CMR) results and the Streptococcus sanguinis(S sanguinis) count and the correlations between the S sanguinis count in oral cavity subgingival plaque and changes in the plasma levels of platelet alpha-granule membrane glycoprotein 140 (GMP-140), fibrinopeptide A (FPA), von Willebrand factor (vWF), and homocysteine (Hcy) in patients with PMVA after increased anti-infective treatment of the oral cavity. This study also discusses the pathogenesis of PMVA from this perspective. The differences in the S sanguinis count in oral cavity subgingival plaque and oral health status between healthy people and PMVA patients will be compared, and the correlation between the oral cavity health status and disease in PMVA patients will be analyzed. Methods: The present randomized controlled trial with a parallel control group will be conducted in 68 PMVA patients diagnosed by the in-patient cardiology department. The selected patients will be randomly divided into 2 groups, one receiving routine drug treatment and the other a combination of anti-infective treatments. The normal control group will comprise 30 healthy people with no infectious oral cavity disease matched by age and sex. We will conduct CMR, and the presence of S sanguinis in subgingival plaques will be used to determine the bacterial count in PMVA patients. Blood samples will also be collected to determine the levels of GMP-140, FPA, vWF, and Hcy. S sanguinis in the subgingival plaque of PMVA patients will be further analyzed after increasing the oral cavity anti-infective treatment; the resulting changes and their correlations with changes in GMP-140, FPA, vWF, and Hcy levels will be assessed. Additionally, the differences in the S sanguinis count and the oral cavity health status of oral cavity dental plaque between healthy people and PMVA patients will be determined, and the correlation between the oral cavity conditions and PMVA will be analyzed. The relationship between the perfusion CMR results and the oral cavity S sanguinis count of PMVA patients, and the potential pathogenesis, will be explored. We will use the SPSS19.0 statistical software package to analyze the data. The measurements will be expressed as means±standard deviation. Student t test will be used for intergroup comparisons, a relative number description will be used for the count data, and the chi-square test will be used for intergroup comparisons. Multivariate logistic regression will be performed to identify associations. A P value < .05 will be considered significant. Discussion: In this study, the correlation between the perfusion CMR results and the S sanguinis count in oral cavity subgingival plaque of PMVA patients will be analyzed. Changes in the levels of GMP-140, FPA, vWF, and Hcy of PMVA patients after receiving increased oral cavity anti-infective treatment will be explored, and the difference in the S sanguinis count in oral cavity subgingival plaque and the oral cavity health status between healthy people and PMVA patients will be compared. 2aTrial registration: Chinese Clinical Trial Registry, (http://www.chictr.org.cn/showprojen.aspx?proj=45091 )